Safety of Conservative Management of High-Grade Squamous Intraepithelial Lesion in Women Under 30 Years Old - Mariana K. Bonas; Michelle G. Discacciati; Hisa M. Videira; Lucas A. Cavalcante; Julio C. Teixeira; Diama B. Vale (Mary Ann Liebert, 2022)
Objectives: To evaluate the outcomes of conservative management in young women with high-grade squamous intraepithelial lesion (HSIL). Methods: A retrospective cohort study included women younger than 30 years referred with HSIL (cytology or biopsy) managed conservatively from 2012 to 2019, in Campinas/Brazil. Regression was the outcome when no evidence of HSIL was observed in at least two consecutive follow-ups. Kaplan?Meyer method was used to determine regression probabilities. Other tests were chi-square or Fisher, Mann?Whitney and COX regression. Results: During the study period, 89 patients were included. No progression to microinvasive or invasive cancer was observed. Sixty-one (69%) patients were younger than 25 years, and 28 (31%) were aged 25?30 years. Spontaneous regression was seen in 64 (72%) and persistence in 25 (28%) of the overall sample. The average time to regression was 15.4 months (standard deviation [SD]?=?7.7), and the follow-up time was 31.6 months (SD 19.0). Age, parity, first sexual intercourse, smoking, hormonal contraception, and colposcopy impression were not different among women with regression or persistence. Regression probabilities were, respectively, 28.9%, 60.2%, and 78.1% after 12, 18, and 24 months. Most of the events happened between 12 and 18 months of follow-up. Conclusions: Conservative management in women younger than 30 years was safe: spontaneous regression was observed in 72% of all women younger than 30 with HSIL managed conservatively. No clinical variable was relevant, influencing regression. In 2 years the regression probability was 78%.